1, 25-(OH)2D3 protects pancreatic beta cells against H2O2-induced apoptosis through inhibiting the PERK-ATF4-CHOP pathway. (26th November 2020) - Hu, Xiaobo; Hu, Cong; Liu, Jun; Wu, Zhuan; Duan, Tingting; Cao, Zhaohui
Abstract: Endoplasmic reticulum (ER) stress plays a critical role in pancreatic β cell destruction which leads to the pathogenesis of type 1 diabetes mellitus (T1DM). Vitamin D (VD) has been reported to reduce the risk of T1DM; however, it remains unknown whether VD affects ER stress in pancreatic β cells. In this study, we investigated the role of the active form of VD, 1, 25-dihydroxyvitamin D3 [1, 25-(OH)2 D3 ], in ER stress-induced β cell apoptosis and explored its potential mechanism in mouse insulinoma cell line mouse insulinoma 6 (MIN6). The results of cell counting kit-8 (CCK8) and flow cytometric analyses showed that 1, 25-(OH)2 D3 caused a significant increase in the viability of MIN6 cells injured by H2 O2 . The protein kinase like ER kinase (PERK) signal pathway, one of the most conserved branches of ER stress, was found to be involved in this process. H2 O2 activated the phosphorylation of PERK, upregulated the activating transcription factor 4 (ATF4) and C/EBP homologous protein (CHOP) expression, and subsequently initiated cell apoptosis, which were significantly reversed by 1, 25-(OH)2 D3 pretreatment. In addition, GSK2606414, a specific inhibitor of PERK, suppressed PERK phosphorylation and reduced the expressions of ATF4 and CHOP, leading to a significant decrease in β cell apoptosis induced by H2 O2 . Taken together, the present findings firstly demonstrated that 1, 25-(OH)2 D3 could prevent MIN6 cells against ER stress-associated apoptosis by inhibiting the PERK-ATF4-CHOP pathway. Therefore, our results suggested that 1, 25-(OH)2 D3 might serve as a potential therapeutic target for preventing pancreatic β cell destruction in T1DM.